ACADEMIC SELF EFFICACY DAN ADVERSITY QUOTIENT PADA MAHASISWA YANG SEDANG MENGERJAKAN SKRIPSI DI UNIVERSITAS KRISTEN SATYA WACANA SALATIGA - Agnes Pasadenia,; Soetjiningsih, Christiana Hari (Jurnal Cakrawala Ilmiah, 2022)
The investigation aims to determine the relationship between academic self-efficacy and adversity quotient in students working on their thesis at Satya Wacana Christian University, Salatiga. This research untiliez the academic self-efficacy scale by Prianto (2010) based on Bandura’s theory and the adversity quotient scale by Boleng (2019) based on Stoltz’s theory. The participant in this study counted 106 studnts according to the number of student who filled out the scale via the google form. Moreover, the level of academic self-efficacy and adversity quotient in students is categorized low. The correlation test results with an r-value of 0,631 with a significance value of p < 0,05. These results demonstrate a positive relationship between academic self-efficacy and advercity quotient. This results can be used as student effort can feel academic self-efficacy when working on their thesis.